2015
DOI: 10.3390/rs71013729
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Changes in Vegetation Activity and Its Driving Factors during the Growing Season in China from 1982 to 2011

Abstract: Using National Oceanographic and Atmospheric Administration/Advanced Very High Resolution Radiometer (NOAA/AVHRR) and Climatic Research Unit (CRU) climate datasets, we analyzed interannual trends in the growing-season Normalized Difference Vegetation Index (NDVI) in China from 1982 to 2011, as well as the effects of climatic variables and human activities on vegetation variation. Growing-season (period between the onset and end of plant growth) NDVI significantly increased (p < 0.01) on a national scale and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 66 publications
4
20
0
Order By: Relevance
“…To confirm the 3 g data set in the study area, we also compared the greening trend with previous studies. During 1982–2011, the average growing‐season NDVI (GSNDVI) of the study area exhibited a non‐significant increase, with a trend of 0.00079 year −1 (Qu et al ., ). In the karst region, maximum annual NDVI increased with a non‐significant slope of 0.0002 year −1 during 1982–2003 (Wang et al ., ), whereas GSNDVI increased significantly at a rate of 0.0015 year −1 during 1982–2013 (Hou et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…To confirm the 3 g data set in the study area, we also compared the greening trend with previous studies. During 1982–2011, the average growing‐season NDVI (GSNDVI) of the study area exhibited a non‐significant increase, with a trend of 0.00079 year −1 (Qu et al ., ). In the karst region, maximum annual NDVI increased with a non‐significant slope of 0.0002 year −1 during 1982–2003 (Wang et al ., ), whereas GSNDVI increased significantly at a rate of 0.0015 year −1 during 1982–2013 (Hou et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…MODIS image time series provide a critically important resource for understanding both the dynamics and the evolution of environmental phenomena (Eastman et al 2013). MODIS data have been widely used in analyses of land cover change over large areas (Zhan et al 2002;Galford et al 2008), vegetation dynamic change and its driving forces in arid and semiarid regions (CampoBescós et al 2013;Li et al 2013;Bao et al 2014;Liu and Lei 2015;Qu et al 2015), and crop mapping and productivity estimation (Wardlow and Egbert, 2008;Mishra and Chaudhuri, 2015). Furthermore, MODIS NDVI time series data have been used to describe regional-scale temporal trends in vegetation by quantifying interannual and seasonal vegetation dynamics (Wardlow and Egbert, 2008;Mishra and Chaudhuri, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As temperatures increased, the date of initiation of the growing season advanced and earlier growth resulted in vegetation covering the land earlier, thus reducing the occurrence of dust storms [87]. However, earlier vegetation growth could increase water stress in the reproductive growth period of water-limited vegetation in the BTSSR [24]. trends for all five subregions recorded slight fluctuations during S 1 .…”
Section: Growing Seasonmentioning
confidence: 96%
“…Following the implementation of this project, more than half of the land in this region has experienced an increase in vegetation productivity during 2000-2010 [23]. Studies on the characteristics of climate change and the response of vegetation cover to weather changes in this region have found that NDVI has recorded a slight increasing trend in the growing season [24,25]. In order to consolidate the results of phase of the Blown-Sand Control Project, and to further reduce sandstorm hazards and construct the northern ecological barrier, phase II has been implemented, spanning the period 2013-2022.…”
Section: Introductionmentioning
confidence: 99%